Synthesis and reactivity of titanium hydrazido(2-) complexes - Selby, J (2009)
This Thesis describes the synthesis and characterisation of titanium hydrazido(2-) complexes and their reactivity towards unsaturated molecules. Exploration of the bonding in titanium hydrazido(2-) complexes is performed through structural and computational studies. Chapter 1 introduces current Group 4 hydrazido chemistry and describes its relevance with comparison to Group 4 imido and mid/late metal hydrazido examples. Chapter 2 describes the synthesis and characterisation of new titanium hydrazido(2-) half-sandwich complexes. A general route to new titanium hydrazido(2-) chemistry is described and suppression of dimerisation pathways common to Group 4 alkyl hydrazido(2-) chemistry is investigated. Chapter 3 describes the synthesis, bonding and preliminary reaction chemistry of a new titanium hydrazido(2-) sandwich complex. Through structural and computational techniques, the bonding in the sandwich complex Cp2Ti(NNPh2)(py) (14) is explored and the implications to the reactivity of this complex considered. Chapter 4 describes the synthesis of new titanium hydrazido(2-) synthons which is extended to the synthesis of new titanium hydrazido(2-) complexes with diamide-amine type ligands. The bonding of the hydrazido(2-) ligand is explored through structural and computational study of these complexes. Chapter 5 describes the novel reaction chemistry of a diamide-pyridyl titanium hydrazido(2-) complex Ti(N2Npy)(NNPh2)(py) (23). Novel reactivity of both the Ti=Nα and Nα-Nβ bonds is presented with the mechanisms of some of these transformations probed by density functional theory (DFT) calculations. Chapter 6 presents full experimental procedures and characterising data for the new complexes reported. CD Appendix contains .cif files for all new crystallographically characterised complexes described.